Instagram-Assisted Language Learning in Islamic Higher Education: Toward Online Collaboration - Yudhiantara , Rully Agung; Nuryantini, Ade Yeti (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2018)
The purpose of this study is to investigate instagram use among English pre-service teachers (EPST) to support their language learning in a particular course. This study sought to explore the following research questions: (1) How do EPST explore instagram to accomplish Online Task-Based Language Learning (OTBLL)? (2) What contents are created and shared by EPST to accomplish OTBLL? To collect the data, this study applied observation and content analysis. In addition several tasks were designed to be accomplished by EPST. The findings shows that EPST were able to integrate both the ability to use instagram and the ability to integrate it for OTBLL. The contents that EPST created and shared met the requirement of OTBLL. The contents included several types: creating video to explain topic assigned, writing phonetic transcription, and other tasks. The results of this study are expected to contribute in improving EPST language skills and their ability to explore social media use for language learning. Being able to seize social media to support language learning is a necessary skill to be nurtured for future language teacher in the 21st century.